RANCANG BANGUN SISTEM INFORMASI SMART LAMP BERBASIS TELEGRAM - suwoto, Donna Olivia; Arnomo, Sasa Ani (LPPM Universitas Putera Batam, 2021)
The existence of technology is to facilitate human work. The advancement of internet technology is currently growing very rapidly. Currently the Internet is not only used as a communication tool but also as a tool to carry out daily activities such as controlling electronic devices, one of which is controlling lights. The owner of the Anugrah Plastik Store has difficulty controlling the lights in his shop because the store is quite far from where he lives. this can take a long time and be quite inconvenient if he forgets to turn off the lights in his shop. Researchers wish to assist shop owners in controlling and unifying lamp conditions remotely by designing a Telegram-based Smart Lamp information system at Anugrah Plastik Shop with the help of the ESP8266 tool. The method used by the author is Extreme Programming with SDLC which consists of planning, design, coding and testing. The results of this study are in the form of a design system that provides convenience in remote light control and provides time efficiency that is much needed by users. In this system there are several additional features, namely the existence of a database that functions to view the history of lamp activity.